Wavelength Converters Placement In All Optical Networks Using Particle Swarm Optimization - Teo , Choon Fang (2005)
Wavelength division multiplexing networks using wavelength-routing have emerged as a popular architectural solution for wide area networks. In this study, we introduce a novel evolutionary algorithm so-called particle swarm optimizer (PSO) to find the optimal solution to the converters placement problem. The major advantage of this algorithm is that it does not need to build up a search tree or to create auxiliary graphs in finding the optimal solutions that have been done recently. In addition, the computed results show that only a few particles are needed to search the optimal solutions of the placement of wavelenght converters problem in an arbitrary mesh network.